The structural changes of the food industry in the European Union - Luljeta Hajderllari; Kostas Karantininis (University of Copenhagen, Department of Food and Resource Economics (IFRO), 2012)
This paper studies the structural changes of food industry in the EU-27. We first provide a detailed description of the relative importance of the various sectors in the food industry. The structure is studied by calculating Gini coefficients for the EU members with regard to food industry. We find that the food industry is one of the most important components of the manufacturing sectors in terms of turnover and employment. Enterprises in the EU are relatively large in terms of turnover but small in the number of enterprises with the dairy and meat sectors being the most important branches of the food industry regarding the share of turnover, employment and enterprises. During the eight years 2000-2007, the Gini coefficient of the food industry in the EU is very close to 1, indicating a high degree of concentration.
Keywords: L66; L6; 330; Food industry; meat; dairy; concentration; EU-25